The Influence of Autonomic Nervous System during Resting State on the Peripheral Pulse Wave Velocity in Young Adult Males - Zainab Nazar Al-Wahab; Ali Fouad Saleem; Bassam Talib Al-Gailani (Wolters Kluwer Medknow Publications, 2024)
Background: The association between the activity of autonomic nervous systems (ANS) and pulse wave velocity (PWV) was commonly deduced after adjusting for confounding factors. The relationship between the ANS and PWV was either maintained, but attenuated, or no longer statistically connected after controlling for confounding variables. Research in young healthy individuals showed that the ANS does not control aortic stiffness (indexed by PWV) in a pressure-independent manner. Therefore, the role of the ANS in controlling PWV is debatable. Objectives: The objective of this study was to examine the possibility that ANS directly affects PWV independent of blood pressure (BP) and heart rate (HR). Subjects and Methods: Thirty-four healthy male volunteers (19 years old) were recruited. Stable brachial systolic BP (SBP)/diastolic BP (DBP) and HR were measured in semi-supine position after a 15-min rest. During the last 5 min, fingertip digital pulse wave (DPW) and lead II electrocardiogram (ECG) signals were recorded. The pulse transit time, and consequently PWV, was calculated by measuring the duration between the ECG R wave climax and a reference point on the DPW in the same cardiac cycle. The ANS activity was assessed by calculating the HR variability (HRV) indices obtained from the ECG record of 5-min R-R intervals (RRIs). Results: HRV indices low-frequency (LF)/high-frequency (HF) (LF band power measured in the 0.04-0.15 Hz)/the HF band power measured in the 0.15-0.4 Hz band) and SD2/SD1 ratios (SD1 and SD2 represent the dispersion along the minor and major axis of the fitted ellipse of the Poincaré plot) (sympathovagal balance) were significantly and positively correlated with PWV. In addition, the standard deviation of RRI, or normal-to-normal "NN" (SDNN) interval, after excluding ectopic beats, the square root of the mean squared differences of successive NN intervals (RMSSD) were significantly and negatively correlated with the PWV. No correlation was obtained between PWV and HR, SBP, or DBP. Conclusion: Peripheral PWV during rest or inactivity is affected directly by the sympathovagal balance independent of BP.